КАРАКАЛПАКСКИЕ ФАМИЛИИ - Ержанова, Д.К. (SCIENCE and SOCIETY, 2025)
The article studies the history of the origin, formation and development of the surname among the Karakalpaks. A lexical-semantic analysis and classification of Karakalpak surnames, their lexical bases are given.
Keywords: names; nomenclature; anthroponymy; surnames; language history; Karakalpak language